Patterns of cigarillo use among Canadian young adults in two urban settings - Yates, Erika A. (Can J Public Health, 2014)
OBJECTIVES: Current estimates indicate that cigarillo use has become commonplace among young adults in Canada despite the established risks to health. However, little else is known about patterns of cigarillo use in this subpopulation. The intent of this research was to examine the patterns, attitudes, and beliefs regarding cigarillo use and co-use of cigarillos and cigarettes among Canadian young adults. METHODS: Canadians aged 19–29 years from the Greater Toronto Area, Ontario and Edmonton, Alberta were recruited from September 2009 to February 2010 and in June 2010, respectively (n=133). Eligible participants completed questionnaires assessing cigarillo, cigarette, and cannabis use; social influence of usage; and beliefs about cigarillo use. RESULTS: Cigarillo use was common in social settings, with friends, and during leisure time. The majority of participants were co-users of cigarillos and cigarettes (82%), and currently used cannabis (72%). Respondents reported “replacing cigarette smoking” and “flavour” as main reasons for smoking cigarillos; and half (52%) believed they were not at all addicted to cigarillos. Disconcertingly, participants perceived the risk of cancer attributed to smoking cigarillos as significantly less than the risk of cancer attributed to smoking cigarettes (p<0.0001). CONCLUSION: These findings highlight the social nature of cigarillo use, and suggest a lack of awareness of the health risks associated with cigarillo and polytobacco use in this small convenience sample of Canadian young adults. Population-level analyses are needed to further investigate cigarillo, polytobacco and concurrent cannabis use patterns and beliefs among Canadian young adults.